Influence of a natural and a synthetic inhibitor of factor XIIIa on fibrin clot rheology - Ryan, EA (1999)
We investigated the origins of greater clot rigidity associated with FXIIIa-dependent cross-linking. Fibrin clots were examined in which cross-linking was controlled through the use of two inhibitors: a highly specific active-center-directed synthetic inhibitor of FXIIIa, 1,3-dimethyl-4,5-diphenyl-2[2(oxopropyl)thio]imidazolium trifluoromethylsulfonate, and a patient-derived immunoglobulin directed mainly against the thrombin-activated catalytic A subunits of thrombin-activated FXIII. Cross-linked fibrin chains were identified and quantified by one- and two-dimensional gel electrophoresis and immunostaining with antibodies specific for the alpha- and gamma-chains of fibrin. Gamma-dimers, gamma-multimers, alpha(n)-polymers, and alpha(p)gamma(q)-hybrids were detected. The synthetic inhibitor was highly effective in preventing the production of all cross-linked species. In contrast, the autoimmune antibody of the patient caused primarily an inhibition of alpha-chain cross-linking. Clot rigidities (storage moduli, G') were measured with a cone and plate rheometer and correlated with the distributions of the various cross-linked species found in the clots. Our findings indicate that the FXIIIa-induced dimeric cross-linking of gamma-chains by itself is not sufficient to stiffen the fibrin networks. Instead, the augmentation of clot rigidity was more strongly correlated with the formation of gamma-multimers, alpha(n)-polymers, and alpha(p)gamma(q)-hybrid cross-links. A mechanism is proposed to explain how these cross-linked species may enhance clot rigidity.